2019
DOI: 10.1016/j.adolescence.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

School environment, physical activity, and sleep as predictors of suicidal ideation in adolescents: Evidence from a national survey

Abstract: Introduction: Suicide is the second leading cause of death among individuals between 10 and 34 years of age and suicidal ideation substantially increases during adolescence. The purpose of this study was to examine the associations among physical activity, sleep, and factors relating to the school environment with adolescent self-reported rates of suicidal ideation on the 2017 National Risk Behavior Survey (YRBS). Methods: A multi-stage cluster sampling procedure was employed to yield a representative sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
5
28
1
2
Order By: Relevance
“…Another study shows novelty in testing the enjoyment of physical activity as a mediator of the social and physical environment in the physical activity of early adolescents based on female gender. This study shows the contribution of the existing literature by identifying several social and physical environmental factors associated with pleasure in physical activity (Budd et al, 2018;Pfledderer, Burns, & Brusseau, 2019). Physical education in secondary schools provides valuable experience and structured physical activity programs (McLennan & Thompson, 2015;Bechter, Dimmock, & Jackson, 2019).…”
Section: Resultsmentioning
confidence: 89%
“…Another study shows novelty in testing the enjoyment of physical activity as a mediator of the social and physical environment in the physical activity of early adolescents based on female gender. This study shows the contribution of the existing literature by identifying several social and physical environmental factors associated with pleasure in physical activity (Budd et al, 2018;Pfledderer, Burns, & Brusseau, 2019). Physical education in secondary schools provides valuable experience and structured physical activity programs (McLennan & Thompson, 2015;Bechter, Dimmock, & Jackson, 2019).…”
Section: Resultsmentioning
confidence: 89%
“…Risky behaviors can develop as unhelpful coping strategies for adolescents with poor mental health and can severely impact their mental well-being [5,8,10,13]. Therefore, it is necessary to pay attention to the quality of an adolescent's relationships within these settings to reduce negative experiences and improve their well-being [14]. The mental health of adolescents is increasingly recognized as an area of priority for public health policies, because it is essential for the future health of the entire population [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…The Guidelines also indicate that moderate to strong evidence shows that physical activity reduces the risk of depression and depressive symptoms ( US Department of Health and Human Services, 2018 ). In a recent study, an association was found between not meeting the physical activity guidelines and increased suicide ideation ( Pfledderer et al, 2019 ). This is also supported by a meta-analysis finding that physical activity is a promising method for reducing suicide ideation ( Vancampfort et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%